Toward Accurate Extraction of Respiratory Frequency From the Photoplethysmogram: Effect of Measurement Site - Hartmann, Vera; Liu, Haipeng; Chen, Fei; Hong, Wentao; Hughes, Stephen; Zheng, Dingchang (Frontiers in Physiology, 2019)
Background: It is known that the respiration-modulated photoplethysmographic (PPG) signals could be used to derive respiratory frequency (RF), and that PPG signals could be measured from different body sites. However, the accuracy of RF derived from PPG signals of different body sites has not been comprehensively investigated. Objective: This study aims to investigate the difference in the accuracy of PPG-derived RFs between measurements from different body sites, respectively for normal and deep breathing conditions. Methods: Under normal and deep breathing patterns, the PPG signals were recorded sequentially in a randomized order from six body sites [finger, wrist under (anatomically volar), wrist upper (dorsal), earlobe, and forehead] of 36 healthy subjects. Simultaneously, the reference respiratory signal was measured by a respiratory belt on the chest. Using the frequency demodulation approach, respiratory signals were extracted from PPG signals for calculating RF by power spectral density. The bias between PPG-derived and reference RFs was then analyzed statistically using analysis of variance and non-parametric tests, Bland-Altman analysis, and linear regression to investigate the difference in RF bias between different sites. Results: The RF bias was significantly influenced by the breathing pattern and measurement site (both p<0.001). Under normal breathing, the RF bias was insignificant in the arm, forehead and wrist under (all p>0.05), and significant in the other sites (all p<0.05). Significant linear relationship between PPG-derived and reference RFs existed at all the sites (p<0.001) except the wrist upper (p>0.05). The linearity between PPG-derived and reference RFs was highest at the forehead (slope of best-fit line: 0.90, R square: 0.64), followed by the earlobe, finger, arm, and wrist under (slope: 0.71, R square: 0.40). Under deep breathing, there was no significant RF bias in all the measurement sites (p>0.05) except forehead (p=0.048). The effect of measurement site on RF bias was not significant (p>0.05). The finger had the smallest RF bias and the narrowest limits of agreement. Conclusion: This study has demonstrated that the accuracy of PPG-derived RF depends on the measurement site and breathing pattern. The best sites are the forehead and finger, respectively for normal and deep breathing patterns.